2022
DOI: 10.48550/arxiv.2205.10764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for Hypodescent in Visual Semantic AI

Abstract: We examine the state-of-the-art multimodal "visual semantic" model CLIP ("Contrastive Language Image Pretraining") for the rule of hypodescent, or one-drop rule, whereby multiracial people are more likely to be assigned a racial or ethnic label corresponding to a minority or disadvantaged racial or ethnic group than to the equivalent majority or advantaged group. A face morphing experiment grounded in psychological research demonstrating hypodescent indicates that, at the midway point of 1, 000 series of morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Charlesworth et al [15] showed that word embeddings concerning race/ethnic groups reveal stereotypes whose valence has remained stable for 200 years. Wolfe et al [52] demonstrated that racial bias reflecting the rule of hypodescent in multi-modal languagevision models is more prominent for women, assigning multiracial female images to the minority group's linguistic label. Wolfe and Caliskan [54] further showed that language-vision models mark the images of women in the language space due to deviation from the default representation of 'person. '…”
Section: Related Workmentioning
confidence: 99%
“…Charlesworth et al [15] showed that word embeddings concerning race/ethnic groups reveal stereotypes whose valence has remained stable for 200 years. Wolfe et al [52] demonstrated that racial bias reflecting the rule of hypodescent in multi-modal languagevision models is more prominent for women, assigning multiracial female images to the minority group's linguistic label. Wolfe and Caliskan [54] further showed that language-vision models mark the images of women in the language space due to deviation from the default representation of 'person. '…”
Section: Related Workmentioning
confidence: 99%